A New Method for Fabrication of Nanohydroxyapatite and TCP from the Sea Snail Cerithium vulgatum - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (HINDAWI LTD, 2014)
Biphasic bioceramic nanopowders of hydroxyapatite (HA) and beta-tricalcium phosphate (TCP) were prepared from shells of the sea snail Cerithium vulgatum (Bruguiere, 1792) using a novel chemical method. Calcination of the powders produced was carried out at varying temperatures, specifically at 400 degrees C and 800 degrees C, in air for 4 hours. When compared to the conventional hydrothermal transformation method, this chemical method is very simple, economic, due to the fact that it needs inexpensive and safe equipment, because the transformation of the aragonite and calcite of the shells into the calcium phosphate phases takes place at 80 degrees C under the atmospheric pressure. The powders produced were determined using infrared spectroscopy (FT-IR), X-ray diffraction, and scanning electron microscopy (SEM). The features of the powders produced along with the fact of their biological origin qualify these powders for further consideration and experimentation to fabricate nanoceramic biomaterials.
Keywords: MECHANICAL-PROPERTIES; NANO-POWDERS; THIN-FILMS; BONE; PHOSPHATE; MICROSTRUCTURE